2020
DOI: 10.3389/fpsyt.2020.00524
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Symptoms and Social Cognition Predict Real-World Outcomes in Patients With Schizophrenia

Abstract: Objective: Real-world functioning is a complex construct influenced by different factors. The impact of social cognition and autism spectrum disorder (ASD) symptoms on different aspects of the life of people with schizophrenia has been demonstrated independently, but it is unclear how these factors are related to functioning when considered concurrently. We hypothesized that ASD symptoms could play a major role in predicting real-world functioning in schizophrenia. Methods: Existent databases from two studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
2
17
1
Order By: Relevance
“…The recognition of emotions, assessed using the TREF, was positively associated with functioning beyond neurocognition and symptoms. This result is consistent with previous reports that showed associations between the recognition of emotions, as measured by the ER-40 and BLERT tasks, and functioning beyond neurocognition 8 , 11 , 25 .…”
Section: Discussionsupporting
confidence: 93%
“…The recognition of emotions, assessed using the TREF, was positively associated with functioning beyond neurocognition and symptoms. This result is consistent with previous reports that showed associations between the recognition of emotions, as measured by the ER-40 and BLERT tasks, and functioning beyond neurocognition 8 , 11 , 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Of note, participants in the “Autistic schizophrenia” group showed greater functional impairment, both at the one-year and at the one-week assessment of the GAF: this result confirms the negative impact of ASD symptoms on functional outcomes of people living with schizophrenia, a fact already attested by studies conducted on larger samples of participants ( 19 21 ).…”
Section: Discussionsupporting
confidence: 75%
“…Subsequent cross‐sectional studies have applied the PAUSS to adults with SCZ, and found that a higher PAUSS score was associated with greater impairment in social cognition (Deste, Vita, Penn, et al, 2020; Vita et al, 2020), social relationships (Deste, Vita, Nibbio, et al, 2020), and self‐reported everyday functioning (Harvey et al, 2019).…”
Section: Resultsmentioning
confidence: 99%